Anti-slip performance of cast steel cable clamps for prestressed cables. (December 2022) - Wang, Zeqiang; Han, Qinghua; Lu, Yan; Hu, Yang
Abstract: The cable structure is a prestressed structure formed by cables constitute structural systems of great practical application in engineering. Cable clamps are the key force transmitting components in the cable structure. Its anti-slip performance will affect the stability of the cable structure. The paper studies the effects of several factors on the anti-slip performance of the cable clamp by experiments. A series of parametric numerical simulations are further carried out. The anti-slip performance of the locked coil cable clamp is the best, and the Galfan coated cable clamp is better and the PE sheathed cable clamp is the worst. The anti-slip capacity of the cable clamp with asymmetric covers is 10%-20% higher than that with symmetric covers. It is also obtained that the bolt preload, the cable tension, the sequence of screwing bolts and stretching the cable and the diameter of the bolt would affect the anti-slip performance of the cable clamp by changing the normal pressure of the cable-clamp interface. And the type of the cable and the cable clamp, the surface treatment of the groove and the thickness of the outer sheath would also affect the anti-slip performance of the cable clamp through changing the property of the contact surface. The anti-slip capacity of the cable clamp is positively correlated with the normal pressure, the closeness of the contact and the friction coefficient of the cable-clamp interface.